Visualizing Knowledge Evolution and Hotspots of Rural Environment and Health: A Systematic Review and Research Direction - Gongrang Zhang; Kang Li; Dongxiao Gu; Xiaoyu Wang; Xuejie Yang; Keyu Zhu; Guoqiang Liang (IEEE Access, 2019)
With global warming, energy scarcity, water shortages, and air, soil, and water pollution, the situation of environments in countries around the world is getting more and more serious and in some countries, rural environmental issues are more prominent. Health problems in rural areas also cannot be ignored, chronic diseases and infectious diseases have become the greatest threat to human life, while good environment and human health are the foundation of social and economic sustainable development. This paper adopts the bibliometrics method to conduct a visual analysis of 6,971 studies in the field of the rural environment and health published on the Web of Science between 2000 and 2017, including time knowledge map analysis, space knowledge map analysis, knowledge base analysis, and research focus analysis. This paper reveals the development status of research in the field of rural environment and health, analyzes, and discusses the research hotspots and future development trends in this field, and provides important knowledge support for researchers to carry out follow-up research.